THE ROLE OF SOCIAL COMPETENCE IN THE PROFESSIONAL ACTIVITY OF FUTURE EDUCATORS OF PRESCHOOL EDUCATIONAL INSTITUTIONS (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The article discusses the importance of social and professional competencies for the implementation of the priority direction of preschool education - socialization; the problem of establishing social relationships with parents, students and teaching staff; a list of competencies that ensure this inclusion; grounds for creating the necessary direction for this.